Investigation of the Demodex Lid Infestation with in Vivo Confocal Microscopy versus Light Microscopy in Patients with Seborrheic Blepharitis. (19th May 2022) - Arici, Ceyhun; Mergen, Burak; Bahar Tokman, Hrisi; Yildiz Tas, Ayse; Tokuc, Edip; Ozturk Bakar, Yesim; Sahin, Afsun
ABSTRACT: Aim: The comparison of the diagnostic efficiency of a reference method (light microscopy [LM] using 10% potassium hydroxide [KOH]) with the use of 100% alcohol to in vivo confocal microscopy (IVCM) for the detection of Demodex eyelid infestation in seborrheic blepharitis patients. Methods: Eyelashes were epilated from the right eyes for the reference method and the left eyes for the alcohol group in 58 eyes of 29 patients. IVCM was used on the left eyes. The primary outcomes were the number of Demodex mites per lash and the rate of Demodex positivity (≥1 mite). Results: The rate of Demodex positivity was similar among the three groups (KOH: 82.8%, alcohol: 86.2%, IVCM: 72.4%; p >.05). The mean number of mites per lash in the KOH group (1.5 ± 1.3) was higher than in the alcohol (0.9 ± 0.6, p =.041) and IVCM groups (0.9 ± 0.9, p =.036). Conclusion: KOH was found to be superior in terms of the quantification of mites compared to alcohol and IVCM.